Gambaran dan Rasionalitas Penggunaan Antibiotik pada Pasien Community Acquired Pneumonia di RSIA Ananda: Studi Retrospektif 2024 - Ashari, Irwan (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2025)
Community Acquired Pneumonia (CAP) remains a major cause of morbidity and mortality, both in children and adults. Empirical antibiotic therapy is the main intervention, but the rationality of its use is often not fully evaluated in primary and secondary care facilities such as RSIA. To determine the pattern and assess the rationality of antibiotic use in pediatric and adult CAP patients at RSIA Ananda. A retrospective descriptive study of medical records of pediatric and adult CAP patients diagnosed with CAP who were treated at RSIA Ananda during January-December 2024. The evaluation of rationality refers to national guidelines from IDAI (Indonesian Pediatrician Association), PAPDI (Indonesian Lung Doctors Association), and drug use indicators from WHO. Of the 134 patients (72 children, 62 adults), all received empirical antibiotic therapy. The antibiotics most commonly given to children were amoxicillin (40.3%) and cefixime (25%), while in adults ceftriaxone (66.1%) and azithromycin (38.7%). A combination of antibiotics was used in 31.8% of cases. The rationality of antibiotic use was assessed as appropriate in 69.4% of children and 74.2% of adults. The most frequent discrepancies found were in the selection of the type and duration of therapy. Although most antibiotic therapy in CAP patients was in accordance with guidelines, there is still room for improvement, especially in the combination, duration, and selection of antibiotics. Fulfillment of the implementation of cross-unit antibiotic management programs is very important.